Birth asphyxia, determinants, and its management among neonates admitted to NICU in Harari and Dire Dawa Public Hospitals, eastern Ethiopia - Sewmehon Amsalu; Merga Dheresa; Yadeta Dessie; Bajrond Eshetu; Bikila Balis (Frontiers Media S.A., 2023)
BackgroundDespite a declining neonatal mortality rate globally, Ethiopia has scored 29-30 deaths per 1,000 live births. Birth asphyxia is a major contributor to neonatal mortality, where 4-9 million newborns develop birth asphyxia each year. This study aimed to assess the prevalence of birth asphyxia, its determinants, and its management among neonates admitted to the NICU in Harari and Dire Dawa public hospitals.MethodsA facility-based cross-sectional study was conducted among 409 randomly selected neonates and their index mothers admitted to neonatal intensive care units of public hospitals in Harari and Dire Dawa from June 20 to August 20, 2021. Data were collected through card review and interviewer-administered questionnaires. The collected data were entered into Epi data version 3.1 and exported to SPSS version 20 for analysis. Logistic regression models were fitted to identify factors associated with birth asphyxia. Adjusted odds ratios along with 95% CIs were estimated to measure the strength of the association, and statistical significance was declared at p-value <0.05.ResultsOne-fifth of neonates [20.8% (95% CI: 16.4, 24.6%)] had birth asphyxia. Neonates born by instrumental delivery (AOR = 2.29, 95% CI: 1.10, 4.76) and neonates born to mother with PIH (AOR = 3.49, 95% CI: 1.47, 8.27), PROM (AOR = 2.23, 95% CI: 1.17, 4.26), and chorioamnionitis (AOR = 3.26, 95% CI: 1.10, 9.61) were more likely to have birth asphyxia compared to their counterpart. Ventilation with a bag and mask 50(58.8), putting on free oxygen 19(22.4), and endotracheal intubation 15(17.6) were taken as management methods.ConclusionOne out of five neonates had birth asphyxia. This urges care providers to adhere to national guidelines of obstetrics and neonatal continuum care. They also need to decrease instrumental delivery and treat PIH, PROM, and chorioamnionitis.